Urinary pesticide biomarkers from adolescence to young adulthood in an agricultural setting in Ecuador: Study of secondary exposure to pesticides among children, adolescents, and adults (ESPINA) 2016 and 2022 examination dataMendeley Data - Rajendra P. Parajuli; Briana N.C. Chronister; Dana Boyd Barr; José Ricardo Suárez-López (Data in Brief)
A widespread reliance on pesticides in agriculture has raised concerns regarding the increased risks of exposure among individuals living in agricultural communities. This article presents urinary pesticide metabolite concentrations for 665 participants in the “Study of Secondary Exposure to Pesticides among Children, Adolescents, and Adults” (ESPINA), which were collected during two follow-up assessments: July to October 2016 (Follow-up Year [FUY]-8b; n = 529) and July to September 2022 (FUY-14a; n = 505) in the agricultural community of Pedro Moncayo, Ecuador. Using first morning void urine samples, concentrations of 19 pesticides or their metabolites were measured including four organophosphates, three pyrethroids, and six neonicotinoids insecticides, two herbicides, two fungicides, and two insect repellents, for the 2016 examination (FUY-8b). In the 2022 examination (FUY-14a), fourteen biomarkers were measured, including four organophosphates, three pyrethroids, three neonicotinoids, two sulfoximines, and one butanolide insecticides, and one herbicide. We present wet weight, urinary-creatinine-adjusted concentrations (2016) and specific-gravity-adjusted concentrations (2016 and 2022).